The Figurative Language in the Poetic Diction of Masuri S.N. and A. Samad Said: A Comparison - A. Hamid, Rahimah (Malay Literature, 2014)
The beauty of a poem depends on the poet's choice of words-his diction-in expressing what his thoughts. Poetic diction is the careful choice of the most apt, beautiful and accurate words to express all kinds of things. A poet's choice of words is closely connected to euphony and the arrangement of words in a certain sequence by the poet. Diction is also closely related to figurative language, that is, the expressions chosen by a poet to beautify his poem, to enhance its effect, and to create certain connotations in it. Careful choice of words, with emphasis on figurative language, or metaphorical expressions, will cause a poem to be beautiful and contain layers of meaning. The approach used here is to look at the choice of words and figurative language in the works of two eminent writers from Malaysia and Singapore, namely A. Samad Said and Masuri S.N. A close comparison of their works will be made to study the strengths and weaknesses of the diction and figurative language in their poems. Keywords: diction, figurative, effect, connotations, beauty